LIP ADHESION- A VIABLE ALTERNATIVE TO PRESURGICAL ORTHODONTICS FOR THE MANAGEMENT OF WIDE CLEFT LIPS IN THIRD WORLD COUNTRIES - Zaidi, Syed Hashim; Rehman, Javed Ur; Rehman, Habib Ur; Ahmed, Naveed (Journal of Ayub Medical College Abbottabad, 2018)
Background: Cleft lip and palate is a relatively common condition presenting a considerable technical challenge, especially the wide cleft (>8mm), for the surgeons. Pre-surgical orthodontics, which reduces the cleft width and facilitates definitive repair, is expensive and not universally available, especially in the third world. Lip adhesion could be a cheaper alternative to pre-surgical orthodontics. Methods: This six-year prospective observational study, from 2010 to 2016, was conducted at the paediatric surgical units of PNS Shifa Hospital, Karachi and Military Hospital Rawalpindi. All children with wide (8 mm or more gap in the alveolus) complete ULCP (unilateral cleft lip and palate) were included in the study. Lip adhesion with concomitant vomer flap palatal repair was followed by definitive lip repair once the desired moulding, i.e., alveolar gap <5 mm or adequate narrowing as per surgeon’s subjective assessment during the 3 and 6 monthly follow up, had been achieved. Results: A total of 53 children with the mean age 4.5±1.5 months were subjected to surgery, 32 (60.4 %) were males and 21 (39.6%) were females. The mean gap in the cleft alveolus was 11.1±1.7 mm, which was reduced to a mean of 3.2±1.3 mm, after a follow up of 4.3±1.1 months. The outcome of the lip repair, based on parental satisfaction, was excellent in 41 (77.3%), good in 10 (18.9%) and poor in 2 (3.8%) cases. Conclusion: Lip adhesion is a safe and effective substitute for pre-surgical orthodontics in wide ULCP. Keywords: Cleft Lip and Palate; Lip Adhesion; Wide cleft